Large electrocaloric effect with high thermal and electric field cycling stability in solution-processed Y:HfO2 thin films. Issue 18 (6th April 2022) - Samanta, Shibnath; Anoop, Gopinathan; Seol, WooJun; Park, Seong Min; Joh, HyunJin; Choi, Je Oh; Ahn, Dante; Unithrattil, Sanjith; Kim, Hoon; Yeom, Jiwon; Hong, Seungbum; Jo, Ji Young
Abstract : Si/Y-HfO2 /Pt shows a large electrocaloric temperature change (Δ T ) of 24.84 K with high reliability on thermal and electrical field cycling. Abstract : The electrocaloric effect (ECE) – the zero-emission energy-efficient process in which an applied electric field can reversibly change the entropy in a polar material, is promising for environment-friendly and compact applications like microelectronic cooling and solid-state refrigeration. For such applications, the ECE material must endure numerous thermal and electric field cycles, and long-term thermal and electric field cycling stability of the ECE material should be investigated in detail. We investigated the performance and reliability of the ECE of solution-processed Y:HfO2 thin films in terms of isothermal entropy change, adiabatic temperature change, isothermal heat and refrigerant capacity under both thermal and electric field cycling. The ECE responses are investigated under thermal (303–423 K) and electric field (10 6 ) cycling processes. A large positive ECE response (temperature change, Δ T max ) of up to 24.8 K (with an ECE strength of 0.7 K cm MV −1 ) was achieved, originating from high polarization and sharp variation in polarization through the phase transition in Y:HfO2 . The isothermal heat ( Q ) and refrigerant capacity (RC) were 7755 J kg −1 and 822 J kg −1, respectively. The Y:HfO2 thin films exhibited robust thermal cycling stability with negligible Δ T max, Q, and RC variations after 40 thermal cycling processes. After 10 6 electric field cycles, Δ T max, Q, and RC were 19.4 K, 6060 J kg −1 and 595 J kg −1, respectively. The large and reliable ECE in environment-friendly lead-free Y:HfO2 thin films deposited directly on a Si-substrate using a facile solution process outperformed the other HfO2 -based and Pb-free ECE materials and will find applications in on-chip microelectronic cooling devices.